Pengaruh Digital Marketing Dan Managerial Capability Terhadap Financial Performance Dengan Competitive Advantage Sebagai Variable Intervening Pada UMKM Tangerang Selatan - Erliana Erliana; Mulyer Mananda Setyahadi (CV. ULIL ALBAB CORP, 2024)
This study analyzes the influence of digital marketing and managerial capability on the financial performance of MSMEs in South Tangerang, with competitive advantage as an intervening variable. A quantitative explanatory approach was used with primary data collected from questionnaires distributed to 100 MSMEs selected through purposive sampling based on specific criteria, such as a minimum of two years of operational experience and the adoption of digital marketing strategies. The analysis was conducted using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method to test direct and indirect relationships among the variables. The results show that competitive advantage has a significant direct effect on digital marketing and the financial performance of MSMEs. Managerial capability also significantly influences digital marketing and financial performance, highlighting the importance of managerial roles in supporting digital marketing strategies. Conversely, operational capability affects only digital marketing without a direct impact on financial performance. Furthermore, digital marketing has not yet proven to be an effective mediator between competitive advantage, managerial capability, and operational capability concerning financial performance. This study recommends strengthening digital marketing strategies and enhancing managerial and operational capabilities to improve the competitiveness and financial performance of MSMEs.